Percutaneous Transarterial Stent Placement in a Transplant Liver Hepatic Artery Complicated by Angioplasty Balloon Rupture and Fragmentation - Vairavamurthy, Jenanan P.; Li, Charles; Urban, Seth; Katz, Michael (Seminars in Interventional Radiology, 2019)
The incidence of posttransplant hepatic arterial stenosis (HAS) has been reported in 5 to 10% of orthotopic liver transplants and, left untreated, can lead to hepatic arterial thrombosis. Most vascular complications develop less than 3 months after initial transplant, with thrombosis representing over half of all complications. There has been a trend toward minimally invasive, endovascular techniques for treating HAS with angioplasty and stenting. In one review of endovascular therapies for HAS, primary technical success was achieved in 95% of the interventions. Complication rates following endovascular repair of HAS have been reported to be between 0 and 23% in the literature. The main risk factors for complications include tortuosity of the hepatic artery and history of a second liver transplant. Other associated risk factors include female gender, age greater than 60 years, prior history of transarterial chemoembolization, and multiple arterial graft anastomoses. The case presented here is representative of a complication of balloon rupture and fragmentation in a patient undergoing hepatic arterial stent placement post–liver transplant.
Keywords: liver transplant; arterial stent; interventional radiology